2003
DOI: 10.1046/j.1365-2141.2003.04757.x
|View full text |Cite
|
Sign up to set email alerts
|

A rapid and specific whole blood HPA‐1 phenotyping by flow cytometry using two commercialized monoclonal antibodies directed against GP IIIa and GP IIb‐IIIa complexes

Abstract: Summary The human platelet antigen 1 (HPA‐1) system has been implicated in rare but severe diseases, such as neonatal alloimmune thrombocytopenic purpura, post‐transfusion purpura and immune platelet refractoriness. We developed a flow cytometry assay for HPA‐1 phenotyping using two commercial monoclonal antibodies, P2 and SZ21, directed against glycoprotein (GP) IIb–IIIa and GP IIIa respectively. One hundred and twenty‐seven healthy controls were studied and ratios of mean fluorescence intensity for P2 and SZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…1 Previous studies had demonstrated that MoAb SZ21 (anti-GPIIIa) bound markedly less to HPA-1b in comparison to HPA-1a PLTs 21 and could, therefore, be used for rapid PLT phenotyping of the HPA-1 system. 22 When we injected MoAb SZ21 over HPA-1a or HPA-1b sensor chips, similar interaction responses (approx. 100 RU) were detected during the association phase ( Fig.…”
Section: Spr Analysis Of Hpa-1a and -1b Antibodiesmentioning
confidence: 91%
“…1 Previous studies had demonstrated that MoAb SZ21 (anti-GPIIIa) bound markedly less to HPA-1b in comparison to HPA-1a PLTs 21 and could, therefore, be used for rapid PLT phenotyping of the HPA-1 system. 22 When we injected MoAb SZ21 over HPA-1a or HPA-1b sensor chips, similar interaction responses (approx. 100 RU) were detected during the association phase ( Fig.…”
Section: Spr Analysis Of Hpa-1a and -1b Antibodiesmentioning
confidence: 91%
“…SZ21, a monoclonal antibody (MoAb) directed against PLT glycoprotein (GP) IIIa, binds at or near the HPA-1a epitope 7-9 . Recently, we developed an in vivo model system in which human PLTs are injected into nonobese diabetic/severe combined immunodeficient (NOD/SCID) mice and allowed to circulate for up to 24 hours 10 .…”
mentioning
confidence: 99%
“…SZ21, a monoclonal antibody (MoAb) directed against PLT glycoprotein (GP) IIIa, binds at or near the HPA-1a epitope. [7][8][9] Recently, we developed an in vivo model system in which human PLTs are injected into nonobese diabetic/severe combined immunodeficient (NOD/SCID) mice and allowed to circulate for up to 24 hours. 10 Using this model, it is possible to investigate the fate of human PLTs in the presence of PLT-reactive antibodies and to examine the potential for novel therapeutics to prevent PLT clearance.…”
mentioning
confidence: 99%
“…5 Phenotyping of HPA 1 on platelets by flow cytometry has been reported. 12,13 Several molecular methods are also available for HPA genotyping.…”
mentioning
confidence: 99%